Influence of Media on Violent Behavior of Child and Youth in Chiangmai Province - รัชตาธนรัชต์ ทัศนมินทร์; วงค์เจริญ ณีรนุช (Journal of Health Science of Thailand, 2021)
The objectives of this study were to investigate the current situation and the influence of media on violent behavior of child and youth. The samples divided into 2 groups: (1) 400 children and youth in Chiangmai Province and (2) 20 children and youth who committed crimes and were detained, and 20 academicians and policy makers of juvenile observation and protection. The research instruments included questionnaire and semi-structured in-depth interview. Data were analyzed by using descriptive statistics, path analysis and content analysis. The findings of this research study revealed that movies, television and internet were the most accessible; and visual and content of media were the factors highly associated with violent behaviors of child and youth. The media, the stimuli of the media, media perception and media learning had statistically significant direct and indirect effects on violent behavior of child and youth (p<0.01). These findings indicated that media perception and media learning should be promoted among child and youth in school; and regular monitoring and evaluation were recommneded.